Sambucus eminagaoglui sp. nov. (Viburnaceae) from Artvin, Türkiye - Beğen, Hayal Akyildirim (Phytotaxa, 2026)
Sambucus eminagaoglui (Viburnaceae) is described as a new species from Northeastern Türkiye. This species is closely related to S. nigra but differs by leaf width, the longer leaf apex, fruit color, and the shape of the leaf base. Molecular analysis using nuclear (ITS) and plastid (rbcL) gene markers further confirmed its classification as distinct species. A detailed description, distribution map, photographs, and a provisional conservation threat status of this newly described species are provided.